VALOR PREDICTIVO DE LA HIPERGLICEMIA EN LA MORTALIDAD DE LOS PACIENTES CON TRAUMATISMO CRÁNEO ENCEFÁLICO - Quito Santos y Col., César (2019)
The work’s aim is to determine wether hyperglicemia has a significative predictive value in the mortality of TEC patients. Fort it In this longitudinal prospective analitical study, we was chose 164 TEC patients. We asumed the value of hyperglicemia as > 160 mg/dL. It was found a mortality rate of 17.1%. From which 82,1% presented hyperglicemia, while among patients who survived only 1,4% presented hyperglicemia, the mortality is higher in patients who presented hyperglicemia, certifying a highly significative asociaton between these 2 variables. The average glicemia level in died patients was 173,4 mg/dL, while the ones who survived was 95,22 mg/dL, evidencing a very significative statistical difference betwen the average of blood glucose level and the mortality of TEC patients. In Conclusion the hiperglicemia, higher than 160 mg/dL is significantly associated to mortality of TEC patients with a positive predictive value of 0,92 anda negative predictive of 0,92.